Hubungan antara Fear of Missing Out (FoMO) dengan Kualitas Tidur Mahasiswa X yang Aktif Bermain TikTok - Putri Suwaibah Safira; Raja Oloan Tumanggor (Lembaga Yasin AlSys, 2026)
High levels of TikTok use among university students have the potential to increase fear of missing out (FoMO) and lead to a decline in sleep quality. This study aimed to examine the relationship between FoMO and sleep quality among university students who are active TikTok users. The research employed a quantitative approach with a correlational design, involving 352 students and using the FoMO Scale and the Pittsburgh Sleep Quality Index (PSQI) as measurement instruments. Regression analysis showed that FoMO had a significant effect on sleep quality, with p = 0.000 and a regression coefficient of B = 0.965. In addition, the R² value of 0.802 indicated that 80.2% of the variance in sleep quality disturbances was explained by FoMO. These findings indicate that higher levels of FoMO are associated with poorer sleep quality among students, as reflected in increased sleep disturbances, delayed sleep onset, and feelings of non-restorative sleep upon waking. The study underscores the importance of managing social media use, particularly TikTok, to maintain healthy sleep among university students.